Determination of User’s Position Using QZSS/GPS Data - Làn, Đào Thị; Dung, Le Tien (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: This paper presents study results of standalone positioning, based on GPS/QZSS observations. For this purpose C1 code observations from STK2 station (IGS station in Japan) were used. Computations in RTKLIB software (RTKPOST module) were executed and SPP method was used to position estimation. In the paper two experiments were realized: firstly user’s position was estimated based on GPS observations, and in the second case QZSS observations were applied also. Preliminary results of positioning accuracy show that GPS/QZSS solution improve accuracy of X coordinate about 0.398 m, accuracy of Y coordinate about 0.432 m and accuracy of Z coordinate about 0.285 m, respectively. Additionally RMS-3D error was estimated based on coordinate differences from GPS and GPS/QZSS solutions. Average value of RMS-3D term equals to 0.986 m, with magnitude order between 0.003 m and 3.649 m. Keywords: GPS, SPP Method. QZSS-Zenith